2022
DOI: 10.1021/acs.inorgchem.2c02919
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Alkynes by a Redox-Active Carboranyl Diphosphine and Formation of Boron-Containing Phosphacycles

Abstract: In this work, we report the reactivity of the carboranyl diphosphine, 1-PtBu2–2-PiPr2-C2B10H10, with terminal alkynes, resulting in the formation of boron-containing phosphacycles. The reported system combines the nucleophilic activation of electron-deficient terminal alkynes via electron-rich phosphine groups with the redox behavior of carborane clusters to promote a sequence of metal-free intramolecular B–H bond activation and cyclization, creating an alkenylphosphonium cycle fused with a reduced open nido-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…A closely related example of bond activation by redox-active 1 was discovered in its reactions with alkynes. 72 We found that electron-deficient terminal alkynes were activated by our system in a process that is driven by cluster reduction and formation of the nido -{C 2 B 10 } cage, yet the products 4a / 4b did not follow the same reactivity pattern as the case described above (Fig. 6).…”
Section: Bond Activations By Carboranyl Diphosphinesmentioning
confidence: 54%
“…A closely related example of bond activation by redox-active 1 was discovered in its reactions with alkynes. 72 We found that electron-deficient terminal alkynes were activated by our system in a process that is driven by cluster reduction and formation of the nido -{C 2 B 10 } cage, yet the products 4a / 4b did not follow the same reactivity pattern as the case described above (Fig. 6).…”
Section: Bond Activations By Carboranyl Diphosphinesmentioning
confidence: 54%
“…For the diamagnetic species present, the 31 P and 11 B NMR spectra of the product indicate that the cluster is still in the open nido - form. We have previously observed the isomerization of the C 2 -symmetric nido- cluster present in 2 into a C s -symmetric nido- cluster during oxidation attempts . The mass spectrum of the reaction mixture provided some information on the composition of the product.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously observed the isomerization of the C 2 -symmetric nido-cluster present in 2 into a C s -symmetric nido-cluster during oxidation attempts. 52 The mass spectrum of the reaction mixture provided some information on the composition of the product. Two major species exhibiting isotope patterns typical for boron clusters were observed: one with smaller intensity, corresponding to the exact mass for 2, and another with larger intensity, corresponding to the loss of one BH unit from 2, thus suggesting a deboronation event.…”
Section: Chemical Oxidation Of 2 With Two Equivalents Of Ferrocenium ...mentioning
confidence: 99%
See 1 more Smart Citation